2017
DOI: 10.31234/osf.io/q28w6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intersentential coreference expectations reflect mental models of events

Abstract: Comprehenders’ perception of the world is mediated by the mental models they construct. During discourse processing, incoming information allows comprehenders to update their model of the events being described. At the same time, comprehenders use these models to generate expectations about who or what will be mentioned next. The temporal dynamics of this interdependence between language processing and mental event representation has been difficult to disentangle. The present visual world eye-tracking experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…We probe comprehenders' expectations prior to the encounter of a disambiguating referential expression, thereby allowing for empirical evidence of prediction in the strict sense of prediction defined by Gambi (2018, p. 1005), namely that the effect is observed prior to disambiguating information in the input. Findings from L1 speakers of English were previously reported in Grüter et al (2018), and showed significant effects indicative of proactive coreference expectations (discussed in more detail below). Here we present results from an equal-sized sample of L2 speakers of English (N = 52), with results showing (i) that the same factor that drove proactive coreference expectations in the L1 group does not appear to do so in the L2 group and (ii) that L2 proficiency does not modulate the pattern of effects.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…We probe comprehenders' expectations prior to the encounter of a disambiguating referential expression, thereby allowing for empirical evidence of prediction in the strict sense of prediction defined by Gambi (2018, p. 1005), namely that the effect is observed prior to disambiguating information in the input. Findings from L1 speakers of English were previously reported in Grüter et al (2018), and showed significant effects indicative of proactive coreference expectations (discussed in more detail below). Here we present results from an equal-sized sample of L2 speakers of English (N = 52), with results showing (i) that the same factor that drove proactive coreference expectations in the L1 group does not appear to do so in the L2 group and (ii) that L2 proficiency does not modulate the pattern of effects.…”
supporting
confidence: 57%
“…Identifying unambiguous effects of prediction satisfying Pickering and Gambi's criterion has been a challenge in research on reference processing. In an attempt to probe more directly for predictive effects in the context of the Goal-bias with transfer-ofpossession events, Grüter et al (2018) used the visual world paradigm to measure L1 English-speaking listeners' eye gaze to event participants during a pause between a sentence about a transfer-of-possession event and a continuation sentence. Results showed a greater preference for looking at the Goal after completed than after ongoing transfer events.…”
Section: Proactive Processing At the Discourse Levelmentioning
confidence: 99%
“…These results contribute to our understanding of the nature of L1 and L2 processing. Recent theoretical proposals hold that L2 processing tends to be less proactive than L1 processing, and that this factor may account for many differences observed between the L1 and the L2 across linguistic domains (RAGE hypothesis, Grüter & Rohde, 2013; Grüter et al, 2014; Grüter, Lew-Williams & Fernald, 2012; Hopp, 2013; Martin et al, 2013). Underlying this notion is the belief that typical L1 comprehension is highly proactive, in that good comprehenders continuously predict upcoming information on the basis of incrementing lexical, semantic and morphosyntactic cues.…”
Section: Discussionmentioning
confidence: 99%
“…A current theoretical hypothesis states that whereas native language processing tends to be highly anticipatory, with comprehenders continuously predicting upcoming information, non-native speakers show a “Reduced Ability to Generate Expectations” (RAGE hypothesis, Grüter & Rohde, 2013; Grüter, Rohde & Schafer, 2014). According to this hypothesis, rather than relying on predictive processing as occurs in L1 comprehension, L2 comprehension primarily relies on a posteriori integration and thus tends to be relatively less proactive than L1 processing.…”
Section: Introductionmentioning
confidence: 99%
“…L1/L2 performance differences have traditionally been attributed to a lack of relevant L2 knowledge, reduced L2 experience, L1 influence, and/or age-of-acquisition effects. Recent attempts to account for L1/L2 differences in sentence-level processing include the idea that, in comparison to L1 processing, L2 processing is impeded by cognitive resource limitations (McDonald, 2006) or slower lexical access (Hopp, in press), a reduced ability to predict (Grüter et al, 2017), reduced sensitivity to grammatical information (Clahsen & Felser, 2006, 2018, or increased susceptibility to memory interference (Cunnings, 2017). These hypotheses are often difficult to disentangle empirically and are not necessarily mutually exclusive.…”
Section: Introductionmentioning
confidence: 99%